Intrathecal RGS4 Inhibitor, CCG50014, Reduces Nociceptive Responses and Enhances Opioid-Mediated Analgesic Effects in the Mouse Formalin Test. (March 2015) - Yoon, Seo-Yeon; Woo, Jiwan; Park, Joon-Oh; Choi, Eui-Ju; Shin, Hee-Sup; Roh, Dae-Hyun; Kim, Key-Sun
<x xml:space="preserve">Abstract</x> BACKGROUND: The regulator of G-protein signaling protein type 4 (RGS4) accelerates the guanosine triphosphatase activity of Gαi and Gαo, resulting in the inactivation of G-protein–coupled receptor signaling. An opioid receptor (OR), a Gαi-coupled receptor, plays an important role in pain modulation in the central nervous system. In this study, we examined whether (1) spinal RGS4 affected nociceptive responses in the formalin pain test, (2) this RGS4-mediated effect was involved in OR activation, and (3) the µ-OR agonist–induced antinociceptive effect was modified by RGS4 modulation. METHODS: Formalin (1%, 20 µL) was injected subcutaneously into the right hindpaws of male 129S4/SvJae×C57BL/6J (RGS4+/+ or RGS4−/−) mice, and the licking responses were counted for 40 minutes. The time periods (seconds) spent licking the injected paw during 0 to 10 minutes (early phase) and 10 to 40 minutes (late phase) were measured as indicators of acute nociception and inflammatory pain response, respectively. An RGS4 inhibitor, CCG50014, and/or a µ-OR agonist, [D-Ala2, N-MePhe4, Gly-ol]-enkephalin (DAMGO), were intrathecally injected 5 minutes before the formalin injection. A nonselective OR antagonist, naloxone, was intraperitoneally injected 30 minutes before the CCG50014 injection. RESULTS: Mice that received the formalin injection exhibited typical biphasic nociceptive behaviors. The nociceptive responses in RGS4-knockout mice were significantly decreased during the late phase but not during the early phase. Similarly, intrathecally administered CCG50014 (10, 30, or 100 nmol) attenuated the nociceptive responses during the late phase in a dose-dependent manner. The antinociceptive effect of the RGS4 inhibitor was totally blocked by naloxone (5 mg/kg). In contrast, intrathecal injection of DAMGO achieved a dose-dependent reduction of the nociceptive responses at the early and late phases. This analgesic effect of DAMGO was significantly enhanced by the genetic depletion of RGS4 or by coadministration of CCG50014 (10 nmol). CONCLUSIONS: These findings demonstrated that spinal RGS4 inhibited the endogenous or exogenous OR-mediated antinociceptive effect in the formalin pain test. Thus, the inhibition of RGS4 activity can enhance OR agonist–induced analgesia. The enhancement of OR agonist–induced analgesia by coadministration of the RGS4 inhibitor suggests a new therapeutic strategy for the management of inflammatory pain.